On the Need and Methods of Researching Various Aspects of Poverty in the Light of the Reflections of Jerzy Topolski - Słodowa-Hełpa, Małgorzata (Studia Historiae Oeconomicae, 2025)
The decision to present selected research problems of poverty in this article through the lens of Professor Jerzy Topolski’s views was primarily motivated by the conviction that, despite the passage of several decades and changes in certain concepts and attitudes towards research in this field, many of his postulates have not lost their relevance and may still inspire not only historians but also researchers from other social science disciplines. The article consists of four parts, two of which, directly relating to the categories of poverty and destitution and the methods of their study, are based on the Professor’s position presented in a lecture delivered in 1991 and published a year later (Topolski, 1992). In the remaining sections, edited on the basis of other works by the Professor, selected theoretical and methodological guidelines and postulates are signaled, which, although no longer directed specifically at poverty researchers, are worth considering from the perspective of their studies. In the first part, against the backdrop of conceptual dilemmas clearly visible in the literature of the subject, the Professor’s stance on treating poverty and destitution as theoretical categories and the boundaries between them resulting from the relationship between needs and the possibilities of meeting them are presented. The second part of the study contains the Professor’s postulates regarding the necessity of moving away from descriptive accounts of poverty and subordinating the narrative to the pursuit of regularities, as well as the role of explanatory and theoretical questions in such proceedings. The third part presents the so-called directive of integral explanation, that is, combining the so-called objective side of the historical process (the effects of human actions) with its subjective side (the actions themselves). The subject of the fourth part is the need to transcend disciplinary boundaries, that is, the interdisciplinary integration of research, of which the Professor was a passionate advocate.